The Role of the Enterprise Resource Planning System (ERP) in General Business Management - Dawood AL Wahabi; Khalid AL Balushi; Ayoub AL Balushi; Dr. Tejas B Vyas (International Journal of Engineering and Management Research, 2024)
This research discusses the topic (the role of the enterprise resource planning (ERP) system in public business management) Oman Broadband Company was used and this study focuses on the role, duties and responsibilities of the ERP system, as this study will focus on the relationship between the ERP system and the effectiveness of business management and also the mechanism of the ERP system’s work. Discuss the topic of the problems and solutions that organizations face during the implementation of the enterprise resource planning system. This research aims to identify enterprise resource planning in the real life of the business environment, and thus valuable information was obtained from the work environment in the Omani Broadband Company and the work was done. Recommendations that help improve the work environment and how to improve and exploit the ERP system.